A Acculturation of Islamic Teachings and Traditional Minang Kabau Locality in Economic Practices - Miswardi Miswardi; Yefri Joni; Nasfi Nasfi (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
a society, values ??that govern life are needed in order to create order in life together. This system of values ??is needed to ensure that the rights of everyone in that society are maintained. The values ??held by the community usually come from something that is highly regarded and respected by everyone in the community. In indigenous peoples, the system of values ??that is believed to be a customary system that originates from reason and mind after the reading process of nature. For religious communities the value system that is believed to be a value system that originates from God's revelation. When the identity of the community is as a customary community and religion, then between religion and custom there is a process of acculturation, although many experts have researched and written about the acculturation between religious and customary teachings, but in this study the researcher saw the acculturation between customary and customary law. as well as religion, especially the customary law and customs of the Minangkabau community which are related to the economic practices of local communities. From the research conducted, it was found that the acculturation of Islamic teachings into the customs of the Minangkabau community because these two values ??have in common some sources, namely reason and nature